Analisis kinerja turbin vortex dengan variasi sudu biomimetik berbentuk rumah keong - Iwan Kurniawan; Alfito Dinova Prayoga; Herisiswanto (BKS-TM Indonesia, 2025)
The demand for renewable energy continues to grow as fossil fuel reserves decline and global energy needs increase. One promising alternative is the vortex turbine, which can operate effectively in low-head regions. This study investigates the effect of blade geometry variations on the performance of a vortex turbine, with a particular focus on curved blades enhanced with spiral-shaped fins inspired by biomimetics. The research was conducted experimentally using three blade types: flat blades, curved blades, and curved blades with additional spiral-shaped fins resembling a snail shell structure. Tests were performed on a laboratory-scale vortex turbine prototype, measuring torque, power, and efficiency. The results showed that the flat blades produced the lowest efficiency (17.6%), the curved blades achieved a moderate efficiency (21.0%), whereas the curved blades with additional spiral-shaped fins reached the highest efficiency (33.01%). The significant improvement observed in the biomimetic blades is attributed to the spiral geometry, which effectively directs the flow, reduces separation, and enhances momentum transfer from the fluid to the blades. These findings demonstrate that the biomimetic approach contributes positively to improving the performance of small-scale vortex turbines, making it a promising solution for renewable energy generation in low-head regions